A colorimetric and fluorometric dual-modal sensor for methanol based on a functionalized pentacenequinone derivative. Issue 60 (11th July 2018) - Zhao, Mengting; Yue, Yuxin; Liu, Chang; Hui, Peiyi; He, Song; Zhao, Liancheng; Zeng, Xianshun
Abstract : A functionalized pentacenequinone derivativeZR1 shows specific selectivity toward methanol via the mechanism of intramolecular charge transfer (ICT). Abstract : A functionalized pentacenequinone derivative, ZR1, as a highly selective sensor for methanol has been prepared. Based on the methanol-induced keto–enol tautomerization of the pentacene-quinone moiety, ZR1 shows specific selectivity toward methanol, which leads to dual-modal detection of methanol with a very low detection limit of 0.038% in ethanol.